Randomized clinical trial to evaluate the efficacy and safety of two types of sandblasted with large-grit and acid-etched surface implants with different surface roughness - Jeon, Jun-Hyung; Kim, Min-Joong; Yun, Pil-Young; Jo, Deuk-Won; Kim, Young-Kyun (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2022)
This study aims to evaluate the efficacy and safety of two types of sandblasted with large-grit and acid-etched (SLA) surface implants with different surface roughness. Patients and.ObjectivesThis study aims to evaluate the efficacy and safety of two types of sandblasted with large-grit and acid-etched (SLA) surface implants with different surface roughness. Patients and.This study was conducted based on a clinical record review of 55 patients (mean age, 53.00 years). A total of 80 SLA surface implants was placed. Among the 80 implants, 38 implants placed in 29 subjects had surface roughness (Ra) of 3.09 μm (test group, TG), while the other 42 implants placed in 31 subjects had a surface roughness (Ra) of 2.50 μm (control group, CG). A comparison was made of implant primary/ secondary stability; success and survival rates; marginal bone loss; and soft tissue assessment including probing pocket depth (PPD), plaque index (PI), gingival index (GI), and bleeding on probing (BOP) between the groups at 1 year after implant placement.MethodsThis study was conducted based on a clinical record review of 55 patients (mean age, 53.00 years). A total of 80 SLA surface implants was placed. Among the 80 implants, 38 implants placed in 29 subjects had surface roughness (Ra) of 3.09 μm (test group, TG), while the other 42 implants placed in 31 subjects had a surface roughness (Ra) of 2.50 μm (control group, CG). A comparison was made of implant primary/ secondary stability; success and survival rates; marginal bone loss; and soft tissue assessment including probing pocket depth (PPD), plaque index (PI), gingival index (GI), and bleeding on probing (BOP) between the groups at 1 year after implant placement.Among the implants that were initially registered, 1 from the TG and 4 from the CG dropped out, leaving 37 implants in the TG and 38 implants in the CG to be traced and analyzed. Although 1 TG case showed unstable primary stability, all cases showed stable secondary stability. Success and survival rates at 1 year after implant placement were 100% in both groups. Marginal bone loss was 0.07 mm and 0.00 mm for the TG and CG, respectively, but the difference was not significant. Among the several parameters for evaluation of soft tissue, the TG showed lower PI at 1 year after implant placement (TG=0.00, CG=0.29; P=0.0004), while the remaining categories showed no significant difference between the groups.ResultsAmong the implants that were initially registered, 1 from the TG and 4 from the CG dropped out, leaving 37 implants in the TG and 38 implants in the CG to be traced and analyzed. Although 1 TG case showed unstable primary stability, all cases showed stable secondary stability. Success and survival rates at 1 year after implant placement were 100% in both groups. Marginal bone loss was 0.07 mm and 0.00 mm for the TG and CG, respectively, but the difference was not significant. Among the several parameters for evaluation of soft tissue, the TG showed lower PI at 1 year after implant placement (TG=0.00, CG=0.29; P=0.0004), while the remaining categories showed no significant difference between the groups.This study shows that the two types of SLA implants with different surface roughness have no difference in efficacy or safety. Therefore, both of the implants can be used safely and with promising outcomes.ConclusionThis study shows that the two types of SLA implants with different surface roughness have no difference in efficacy or safety. Therefore, both of the implants can be used safely and with promising outcomes.